PESONA SEGARA-GUNUNG SEBAGAI KEUNGGULAN DALAM PENGEMBANGAN DESA WISATA LES, KABUPATEN BULELENG, BALI - Widari, Dewa Ayu Diyah Sri; Dewa Putu Oka Prasiasa (Journal of Tourism Destination and Attraction, 2024)
Segara-gunung is a concept in the development of Les Tourism Village which makes beaches and mountains an advantage of tourist attractions in supporting sustainable tourism development. This study uses a qualitative descriptive method. The data collection techniques used are observation, interviews and document study. The technique for determining informants is purposive sampling, with a total of 9 informants. This study aims to analyze the potential of Les Tourism Village which offers beach and mountains as tourist attraction advantages. The results show that the beach area on the north side of the village is not only used as a livelihood for local residents, but is also packaged into tourist attractions such as snorkeling and diving. Another charm that Les Tourism Village has is the mountainous area on the south side of the village. Tourists can visit waterfalls, hiking tours, see the charm of caves. Tourists can also witness the process of making traditional products in sugar tourist activities, Bali Arak tours, salt making tours, and kele honey tours. The community uses local ingredients in producing juruh sugar, Balinese Arak, salt and kele honey, the manufacturing process is traditionally carried out as an effort to preserve the heritage of ancestors, it can also play a role in supporting the development of sustainable tourism.